Eubicarbonatemic Hydrogen Ion Retention and CKD Progression - Nicolaos E. Madias (Kidney Medicine, 2021)
Small-scale trials in patients with chronic kidney disease (CKD) 3-5 have shown that hypobicarbonatemic metabolic acidosis promotes progression of CKD. Accordingly, the 2012 KDIGO (Kidney Disease: Improving Global Outcomes) guideline suggests base administration to patients with CKD when serum bicarbonate concentration ([HCO3ˉ]) is <22 mEq/L (~15% of non–dialysis-dependent patients with CKD). However, individuals with milder CKD largely maintain serum [HCO3ˉ] within the normal range (eubicarbonatemia) and yet can manifest hydrogen ion (H+) retention. Limited data in eubicarbonatemic patients with CKD 2 suggest that base administration ameliorates CKD progression. Furthermore, most patients with moderate and advanced CKD maintain a normal serum [HCO3ˉ], and of those, the vast majority most likely harbor masked H+ retention. The present review probes this expanded concept of metabolic acidosis of CKD: the eubicarbonatemic H+ retention or subclinical metabolic acidosis of CKD. It focuses on the high prevalence of the entity, its pathophysiologic features, its clinical course, and recent work on potential biomarkers of the condition. Further, it puts forward the urgent task of investigating definitively whether treatment with alkali of eubicarbonatemic H+ retention delays CKD progression. If proven true, such knowledge would trigger a paradigm shift in the indication for alkali therapy in CKD.